ANALISIS GAYA KEPEMIMPINAN SITUASIONAL DAN DAMPAKNYA TERHADAP MOTIVASI KERJA GURU DI KABUPATEN JAYAPURA - Wattimena, Janty; Dwikurnianingsih, Yari; Sugiarto, Agus (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2025)
This study aims to analyze the influence of situational leadership style on teacher work motivation in Jayapura Regency. Using a quantitative approach, the research method applied is a survey, involving 10 teachers of SD Negeri Inpres Sereh. The data collection technique was carried out by distributing questionnaires consisting of two main parts: one to measure situational leadership style and one to evaluate teacher work motivation. The results of the study indicate that there is a significant positive relationship between situational leadership style and teacher work motivation. This study also identified that leaders who are able to adapt to the needs and level of teacher readiness tend to increase their enthusiasm and commitment to their work. The discussion indicates that the application of a flexible and responsive leadership style can create a more supportive work environment, thus encouraging teachers to innovate and actively participate in the teaching and learning process. The conclusion of this study is that situational leadership style has a significant and positive influence on teacher work motivation in SD Negeri Inpres Sereh, Jayapura Regency. Therefore, it is recommended for principals and educational leaders to apply an adaptive leadership style to improve teacher motivation and performance in learning.